Agriculture and the Nitrogen Cycle: Assessing the Impacts of Fertilizer Use on Food Production and the Environment - Arvin Mosier, J. Keith Syers, John R. Freney (Island Press, 2013)
Nitrogen is an essential element for plant growth and development and a key agricultural input-but in excess it can lead to a host of problems for human and ecological health. Across the globe, distribution of fertilizer nitrogen is very uneven, with some areas subject to nitrogen pollution and others suffering from reduced soil fertility, diminished crop production, and other consequences of inadequate supply. Agriculture and the Nitrogen Cycle provides a global assessment of the role of nitrogen fertilizer in the nitrogen cycle. The focus of the book is regional, emphasizing the need to maintain food and fiber production while minimizing environmental impacts where fertilizer is abundant, and the need to enhance fertilizer utilization in systems where nitrogen is limited. The book is derived from a workshop held by the Scientific Committee on Problems of the Environment (SCOPE) in Kampala, Uganda, that brought together the world's leading scientists to examine and discuss the nitrogen cycle and related problems. It contains an overview chapter that summarizes the group's findings, four chapters on cross-cutting issues, and thirteen background chapters. The book offers a unique synthesis and provides an up-to-date, broad perspective on the issues of nitrogen fertilizer in food production and the interaction of nitrogen and the environment.